Post-test comparison of HIV test knowledge and changes in sexual risk behaviour between clients accessing HIV testing online versus in-clinic. (13th January 2019) - Salway, Travis; Thomson, Kimberly; Taylor, Darlene; Haag, Devon; Elliot, Elizabeth; Wong, Tom; Fairley, Christopher K; Grennan, Troy; Shoveller, Jean; Ogilvie, Gina; Gilbert, Mark
Abstract : Objective: Internet-based HIV testing offers the potential to address privacy-related barriers to testing and increase frequency of testing but may result in missed opportunities related to sexual health education and prevention that typically occur in face-to-face encounters. In this study, we assessed the HIV test knowledge and sexual risk behaviour of clients testing for HIV through GetCheckedOnline, an internet-based sexually transmitted and bloodborne infection testing platform inclusive of HIV testing, in comparison to clients testing through a large sexual health clinic. Methods: We concurrently recruited GetCheckedOnline clients and clinic clients from Vancouver, Canada, over the course of a 10-month period during 2015–2016. Participants completed baseline and 3-month questionnaires, anonymous and online. A six-item score was used to estimate knowledge of HIV test concepts typically conveyed during an HIV pretest encounter in a clinic. We used multiple regression to estimate associations between testing modality (online vs clinic based) and two outcomes—HIV test knowledge and change in condom use pre/post-test—with adjustment for relevant background factors. Results: Among 352 participants, online testers demonstrated higher HIV post-test knowledge than clinic-based testers (mean score 4.65/6 vs 4.09/6; p<0.05); this difference was reduced in adjusted analysis (p>0.05). Men who have sex with men, clients with a university degree, those who have lived in Canada >10 years and English speakers had higher HIV post-test knowledge (p<0.05). Eighteen per cent of online testers and 10% of clinic-based testers increased condom use during the 3 months post-test (p>0.05). Conclusions: In this comparative study between online and clinic-based testers, we found no evidence of decreased HIV test knowledge or decreased condom use following HIV testing through GetCheckedOnline . Our findings suggest that with careful design and attention to educational content, online testing services may not lead to missed opportunities for HIV education and counselling.